2021
DOI: 10.2320/matertrans.mt-m2020254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fe<sup>3+</sup> on the Corrosion Behavior of High-Purity Aluminum in Neutral Solutions Containing Cl<sup>−</sup>

Abstract: In this study, the effects of Fe 3+ on corrosion behavior of high-purity aluminum (Al) were investigated in aqueous NaCl solutions containing Fe 3+ using immersion tests, electrochemical analysis, and surface observations. For high-purity Al immersed in an Fe 3+ solution, the open circuit potential was much lower and the corrosion rate was higher than that of high-purity Al in a solution without Fe 3+ . The corrosion morphology of high-purity Al after immersion in the test solutions containing Fe 3+ was mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Figure 5 d shows the NSS corrosion for 240 h. EDS analysis of the corrosion products inside the pitting reveals that the predominant components are O and a small amount of Al, with overlapping states of the corrosion product Al(OH) 3 . Compared to 144 h, the number of cracks on the metal matrix surface decreases, and the corrosion behavior at the interface is mainly characterized by the healing of small cracks on the passivation film [ 28 ]. With the extension of NSS exposure, the oxide film on the metal surface gradually thins.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 d shows the NSS corrosion for 240 h. EDS analysis of the corrosion products inside the pitting reveals that the predominant components are O and a small amount of Al, with overlapping states of the corrosion product Al(OH) 3 . Compared to 144 h, the number of cracks on the metal matrix surface decreases, and the corrosion behavior at the interface is mainly characterized by the healing of small cracks on the passivation film [ 28 ]. With the extension of NSS exposure, the oxide film on the metal surface gradually thins.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, as the NaCl concentration increases, H evolution in the AA7075 decreases, aligning with the galvanic current's behavior, as shown in Figure 4. The autocatalytic dissolution process on the CS1018 side [41,[70][71][72][73] primarily occurs in diluted solutions, resulting in the accelerated corrosion of AA7075, as shown in Figure 4. Previous research has demonstrated that, when AAs are immersed in NaCl solutions, the presence of Fe species results in the formation of a less efficient protective film consisting of Al(OH) and Fe(OH) , which significantly reduces the corrosion resistance of AAs [73].…”
Section: Resultsmentioning
confidence: 99%
“…The autocatalytic dissolution process on the CS1018 side [41,[70][71][72][73] primarily occurs in diluted solutions, resulting in the accelerated corrosion of AA7075, as shown in Figure 4. Previous research has demonstrated that, when AAs are immersed in NaCl solutions, the presence of Fe species results in the formation of a less efficient protective film consisting of Al(OH) and Fe(OH) , which significantly reduces the corrosion resistance of AAs [73]. As a result, a higher concentration of Fe chemical species generated by the self- The autocatalytic dissolution process on the CS1018 side [41,[70][71][72][73] primarily occurs in diluted solutions, resulting in the accelerated corrosion of AA7075, as shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In association with the awarded papers introduced above, popular topics that Materials Transactions published in recent years are grain boundary segregation 93) as Ito et al were concerned with, 4,30,49) creep deformation in a wide range of materials 94102) including tricrystals by Okada et al 103,104) and work hardening in various forms of deformation in an aluminum single crystal, 105) an A3104 aluminum alloy, 106) a Ti6Al4V alloy 107) and high-strength steels. 108) Furthermore, pitting corrosion resistance is also a popular issue reported by many research groups in terms of corrosion behavior of pure aluminum, 109) pure zirconium 110) and stainless steels. 111113) Readers who are interested in such topics may be worth checking them.…”
Section: Editor's Remarksmentioning
confidence: 99%